Kajian Potensi Sektor Pariwisata Untuk Meningkatkan Pendapatan Asli Daerah di Kabupaten Tanah Bumbu - Yulanda, Akhmad Tomy; Dewi Rahayu (PPJP ULM, 2019)
This study aims to determine the potential and development of the tourism sector to local revenues in Tanah Bumbu Regency as well as the efforts of the Regional Government of Tanah Bumbu Regency in managing and developing the tourism sector to increase Regional Original Revenue. The research method used is quantitative descriptive method. The results of the study show that strategic location and the support of the government and private parties and the surrounding communities of tourism objects can beutilized for business development and services in Tanah Bumbu Regency.